Human Ribosomal Proteins RPeL27, RPeL43, and RPeL41 Are Upregulated in Nasopharyngeal Carcinoma Cell Lines - Sim, E.U.H.; Chan, S.L.L.; Ng, K.L.; Lee, C.W.; Narayanan, K. (Hindawi Publishing Corporation, 2016)
Apart from their canonical role in ribosome biogenesis, there is increasing evidence of ribosomal protein genes’ involvement in various cancers. A previous study by us revealed significant differential expression of three ribosomal protein genes (RPeL27, RPeL41, and RPeL43) between cell lines derived from tumor and normal nasopharyngeal epithelium. However, the results therein were based on a semiquantitative assay, thus preliminary in nature. Herein, we provide findings of a deeper analysis of these three genes in the context to nasopharyngeal carcinoma (NPC) tumorigenesis. Their expression patterns were analyzed in a more quantitative manner at transcript level. Their protein expression levels were also investigated. We showed results that are contrary to previous report. Rather than downregulation, these genes were significantly overexpressed in NPC cell lines compared to normal control at both transcript and protein levels. Nevertheless, their association with NPC has been established. Immunoprecipitation pulldown assays indicate the plausible interaction of either RPeL27 or RPeL43 with POTEE/TUBA1A and ACTB/ACTBL2 complexes. In addition, RPeL43 is shown to bind with MRAS and EIF2S1 proteins in a NPC cell line (HK1). Our findings support RPeL27, RPeL41, and RPeL43 as potential markers of NPC and provide insights into the interaction targets of RPeL27 and RPeL43 proteins.